2016
DOI: 10.1016/j.healthplace.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of neighborhood social capital on life satisfaction and self-rated health: A possible pathway for health promotion?

Abstract: Neighborhood social capital has repeatedly been linked to favorable health-outcomes and life satisfaction. However, it has been questioned whether it's impact on health has been over-rated. We aim to investigate relationships between neighborhood social capital and self-rated health (SRH) and life satisfaction (LS) respectively, both directly and indirectly mediated via Sense of Coherence and self-esteem. Based on a cross-sectional population-survey (N=865) in a medium size Norwegian municipality, we specified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 37 publications
0
42
0
3
Order By: Relevance
“…By contrast, increased access to social capital can lead to improvements in depression (Webber et al, 2011) and self-rated health (Verhaege et al, 2012). Maass et al (2016) also found self-rated health to be related to socio-demographic variables that favoured those in higher…”
Section: One: Social Systems Generate Inequality Over the Life Coursementioning
confidence: 90%
See 1 more Smart Citation
“…By contrast, increased access to social capital can lead to improvements in depression (Webber et al, 2011) and self-rated health (Verhaege et al, 2012). Maass et al (2016) also found self-rated health to be related to socio-demographic variables that favoured those in higher…”
Section: One: Social Systems Generate Inequality Over the Life Coursementioning
confidence: 90%
“…Social capital has been conceptualised as encompassing access to cooperative, trusted relationships and resources, civic engagement, and opportunities for reciprocity (Maass, Kloeckner, Lindstrøm, & Lillefjell, 2016;Webber, Huxley & Harris, 2011;Abbott, 2010;Lochner, Kawachi & Kennedy, 1999). It relates to the ability to access benefits that help improve the living standards of an individual or community (Carillo Alvarez & Riera Romani, 2017;Eriksson & Ng, 2015;Putnam, 2000;Lochner et al, 1999;Portes, 1998).…”
Section: Social Capitalmentioning
confidence: 99%
“…Numerous studies have found significant associations between social capital and various health behaviours and outcomes, such as self-assessed health [16][17][18], mental health and well-being [12,19], psychological distress [13], cardiovascular and cancer mortality [20], vegetable and fruit consumption [21], physical activity [22], and smoking cessation [23][24][25]. It has been suggested that social capital can influence health through various mechanisms [2].…”
Section: Social Capital and Healthmentioning
confidence: 99%
“…En la dimensión de motivación o capital social cognitivo, la confianza, confiabilidad, respeto, identificación, cooperación, solidaridad y en general los valores que las personas atribuyen a sus relaciones con los demás miembros de su comunidad, influye en la satisfacción con la vida en general, por lo que promover el capital social en una comunidad puede ser una estrategia beneficiosa para promoverla (Diener et al, 2009;Maass, et al, 2016;Rablen, 2012).…”
Section: Capital Social Cognitivo Y Los Dominios De La Vidaunclassified